HUBUNGAN ANTARA KEHARMONISAN KELUARGA DENGAN KONSEP DIRI SISWA KELAS X SMK N 1 SUMATERA BARAT SEMESTER GENAPTAHUN AJARAN 2021/2022 - Putri, Nur Syahadani; Ariani, Fitria; Putri, Ananda Maha; Yulia, Niken Gusta (Journal Prakarsa Paedagogia, 2022)
Abstract:This study aims to determine the relationship between family harmony and self-concept of class X students of SMK N 1 West Sumatra. The type of research used in this research is quantitative with the type of correlational research. The population in this study was class X SMK N 1 West Sumatra 420 students, the sample in this study was class X SMK N 1 West Sumatra 205 students, the technique used in this study was random (Random Sampling), the variables studied in this study were random sampling. In this study, family harmony with self-concept.This study examines the relationship between family harmony and self-concept. Quantitative research is the systematic scientific study of graphs and phenomena and relationships. The instrument used in collecting data in this study was a questionnaire that was compiled according to a Likert scale model. Data analysis was performed using statistical programs on SPSS 20 computer and Microsoft Excel. Based on the results of the hypothesis, the calculated r value is 0.151 while the r table value is 0.138 because the calculated r value is greater than r table (0.1510.138) there is a relationship between Family Harmony and Self-Concept. Keywords: Family Harmony, Self Concept